Elucidating the pathogenesis of adenosine deaminase 2 deficiency: current status and unmet needs. (2nd December 2021) - Tarrant, Teresa K; Kelly, Susan J.; Hershfield, Michael S
ABSTRACT: Introduction: Humans have two adenosine deaminase isozymes, ADA1 and ADA2, which differ in affinity for their substrates, adenosine (Ado) and 2ʹdeoxyadenosine (dAdo), and their localization. Inherited deficiencies of ADA1 and ADA2 compromise different aspects of immune and hematological function. The metabolic consequences of ADA1 deficiency show that its enzymatic (ADA) activity is central to its biological function. By contrast, the function of ADA2 is uncertain and no direct metabolic consequences of the deficiency of ADA2 (DADA2) have yet been identified. Several potential pathogenetic mechanisms related to, or independent of, ADA2 enzymatic activity have been proposed. Areas covered: We will review the discovery of ADA2 and DADA2, and two principal hypotheses: that ADA2 regulates the concentration of extracellular Ado and/or that it is a growth factor. We will consider two newer proposals that involve the effects of ADA2 products rather than its substrates, one of which postulates a pathogenic role for elevated levels of ADA2. Expert opinion: Some currently proposed mechanisms of DADA2 pathogenesis are controversial or contradictory, and supportive evidence is inadequate. Progress in several areas may clarify the function of ADA2 and facilitate the development of new therapies for DADA2 based on elucidation of its pathogenesis.